2014
DOI: 10.1108/qrom-10-2012-1103
|View full text |Cite
|
Sign up to set email alerts
|

Exploring identity: a figurative character image-elicitation approach

Abstract: Purpose – The purpose of this paper is to explore the potential of incorporating visual methods in the study of identity and identity work. Design/methodology/approach – Scholars have proposed a range of approaches to the study of identity. However, studies have typically relied on interviews or surveys with little exploration of the dynamic narrating of self-in-situ inherent to identity and identity work. The paper reviews the aforement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…In fact, this approach turned out to be much more fruitful as we felt we were giving 'voice' to each drawing instead of trying to see them as representing certain categories (Davison et al, 2012;Samuels, 1993). What is more, although prior research (Bryans and Mavin, 2006;Butler et al, 2014;Comi et al 2014;Vince and Broussine, 1996) seems to suggest drawings and visuals in general can serve as triggers for further elaboration through talk, here we are treating the drawings as their authors' way of making sense of their local professional context (Ibarra and Andrews, 1993;Meyer 1991;Stigliani and Ravasi, 2012).…”
Section: Analysing the Drawingsmentioning
confidence: 93%
See 1 more Smart Citation
“…In fact, this approach turned out to be much more fruitful as we felt we were giving 'voice' to each drawing instead of trying to see them as representing certain categories (Davison et al, 2012;Samuels, 1993). What is more, although prior research (Bryans and Mavin, 2006;Butler et al, 2014;Comi et al 2014;Vince and Broussine, 1996) seems to suggest drawings and visuals in general can serve as triggers for further elaboration through talk, here we are treating the drawings as their authors' way of making sense of their local professional context (Ibarra and Andrews, 1993;Meyer 1991;Stigliani and Ravasi, 2012).…”
Section: Analysing the Drawingsmentioning
confidence: 93%
“…Our purpose here is to contribute to studies looking at creative industries from the clustering perspective (Grodach et al, 2014;Lin, 2017Lin, , 2018. Research has shown that drawings have the potential to make the subconscious tangible (Bryans and Mavin 2006), explore identities and identity work (Butler et al 2014), as well as stimulate interview settings (Comi et al, 2014), but to the best of our knowledge, and apart from the literature on network pictures (Henneberg et al, 2006(Henneberg et al, , 2010, drawings have not been extensively utilised when investigating various organisational forms and phenomena. At the same time, however, a recent study (Boix, Hervás-Oliver, and De Miguel-Molina, 2015) on clustering in the creative industries highlighted the importance of studying clustering by drawing on novel research methods, and as such, one of the aims of this paper is to illustrate how visual methods can increase our body of knowledge on creative industries.…”
Section: How Do Individuals Embedded In a Local Ecosystem Make Sense Out Of It And What Does This Tell Us About The Perceptions Of And Comentioning
confidence: 99%